Conjugation of hydrophobic moieties enhances potency of antisense oligonucleotides in the muscle of rodents and non-human primates. Issue 12 (11th May 2019) - Østergaard, Michael E; Jackson, Michaela; Low, Audrey; E. Chappell, Alfred; G. Lee, Richard; Peralta, Rachel Q; Yu, Jinghua; Kinberger, Garth A; Dan, Amy; Carty, Rick; Tanowitz, Michael; Anderson, Patrick; et al.
Abstract: We determined the effect of attaching palmitate, tocopherol or cholesterol to PS ASOs and their effects on plasma protein binding and on enhancing ASO potency in the muscle of rodents and monkeys. We found that cholesterol ASO conjugates showed 5-fold potency enhancement in the muscle of rodents relative to unconjugated ASOs. However, they were toxic in mice and as a result were not evaluated in the monkey. In contrast, palmitate and tocopherol-conjugated ASOs showed enhanced potency in the skeletal muscle of rodents and modest enhancements in potency in the monkey. Analysis of the plasma-protein binding profiles of the ASO-conjugates by size-exclusion chromatography revealed distinct and species-specific differences in their association with plasma proteins which likely rationalizes their behavior in animals. Overall, our data suggest that modulating binding to plasma proteins can influence ASO activity and distribution to extra-hepatic tissues in a species-dependent manner and sets the stage to identify other strategies to enhance ASO potency in muscle tissues.